Responsibility of the Entrepreneurial Association for Micro, Small and Medium Enterprises on Car Free Day in Cilegon City - Sulasno; Lolitawati; Pratama, Putri (KRTHA BHAYANGKARA, 2025)
Paguyuban Wirausaha Cilegon is an association that oversees Micro, Small and Medium Enterprises activities that focus on the car free day activity area. This study aims to determine the utilization and development as well as legal responsibility for Micro, Small and Medium Enterprises located in the car free day area. This study uses a qualitative method with an empirical legal approach. Primary data sources come from Paguyuban Wirausaha Cilegon while secondary data comes from books, journals, encyclopedias, dictionaries, and virtual sources. while data analysis uses analytical descriptive, The results of this study indicate that the utilization and development of Micro, Small and Medium Enterprises in the car free day area can be done by making visitors more interested in coming to the car free day area by providing music facilities, facilities for blood donors, health checks and so on which aim to provide comfort and good benefits for the community, as well as development in marketing, Micro, Small and Medium Enterprises have carried out marketing online, by pre-ordering products, and the legal responsibility carried out by the Cilegon Entrepreneurial Association for Micro, Small and Medium Enterprise products can be done by registering employment, Business Identification Number, Halal certificate, BPOM, and intellectual property.